Diseño de un código de convivencia para el mejoramiento de las relaciones interpersonales en el Colegio Nacional Mixto El Quiteño Libre - Tigua Chipantiza, Ana María (2013)
Begins with the construction of the problem based on the institutional background that reveal their reality, and their actors within their respective areas. To make the diagnosis explains the different application of methodology to an approach to the problem of the state, while it is a prioritization of the current needs. The importance of the research lies in the need to solve the problem and the usefulness of the expected results, showing the benefits and advantages to be derived from the development of a Code of Coexistence, in addition to the objectives arising from the needs analysis actual institution and the urgency of solving, research is supported by a legal Framework consists of the set of documents of legal nature that serve as testimony referential, and a theoretical framework that provides a set of concepts that guide the construction of product.